Divergence in morphology, calls, song, mechanical sounds, and genetics supports species status for the Inaguan hummingbird (Trochilidae: Calliphlox "evelynae" lyrura). (17th December 2014) - Feo, Teresa J.; Musser, Jacob M.; Berv, Jacob; Clark, Christopher James
Abstract: The Bahama Woodstar ( Calliphlox evelynae ), a hummingbird endemic to the Bahama Archipelago, comprises two currently recognized subspecies: Calliphlox e. evelynae, found throughout the Bahamas and in the Turks and Caicos Islands, except on Great and Little Inagua; and C. e. lyrura, named for its unique, lyre-shaped outer tail feathers and found only on the islands of Great and Little Inagua. The two were originally described as separate species, partly on the basis of their divergent tail morphology, but were subsequently lumped by Peters (1945) . These taxa are members of the North American "bee" hummingbird clade, which produce mechanical sounds with their tails during courtship displays. Changes in tail shape may produce significant acoustic divergence. To determine the extent of differentiation between lyrura and evelynae, we collected field recordings of calls, songs, and courtship displays from New Providence and Great Inagua islands and surveyed morphological variation across the archipelago. We sequenced 4 nuclear loci and 2 mitochondrial genes from 9 individuals of evelynae and 6 individuals of lyrura . Both sexes of lyrura and evelynae can be diagnosed by vocal calls, and males can be diagnosed by morphology, song, and courtship display. Phylogenetic reconstructions based on the genetic data indicate that the 2 populations are reciprocally monophyletic and that they diverged ∼0.69 mya. Our data indicate that lyrura is a unique evolutionary lineage that warrants species status under both the phylogenetic and the biological species concept.